Teachers’ Tablets Use in Facilitating Students’ Learning in Public Secondary Schools in Karatu District, Tanzania: A Concurrent Mixed-Methods Study - Baha, Paskali; Almasi, Mustapha; Kihwele, Jimmy Ezekiel (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study explored teachers’ tablet use in facilitating students’ learning in public secondary schools after the government had distributed them to all teachers. The focus was on understanding how teachers learn to use tablets in teaching, how they use them, and the challenges they encounter. The study employed a concurrent mixed design with a sample of 211 selected respondents from government secondary schools. Data collection employed questionnaires, interviews, and observation methods, and the analysis involved descriptive statistics and thematic analysis. The findings revealed that teachers use tablets primarily for teaching and information searching, and rarely for entertainment. Specific teaching activities for teachers using tablets include searching and downloading teaching materials and delivering lessons, despite 67% of teachers have not received formal training on using tablets. Teachers learn to use tablets through self-initiative and assistance from fellow teachers, while facing limited internet connectivity, insufficient training, and technical issues with the tablets. The findings imply that continued ICT use without adequate TPACK skills among teachers risks the quality of teaching and digital integration in the era of technological advancement. The findings call for interventions to help teachers embrace the power of technology in teaching.